A critical review of Islamic deposit and financing transactions - Saleem, Muhammad Yusuf (2011)
This paper focuses on issues of form and substance in Islamic deposit and financing transactions. It critically analyses the deposit and financing products of Islamic banks. It argues that a transaction establishes a certain contractual relationship between the parties and entitles them to certain rights and obligations. This paper argues that issues related to substance in transactions are directly concerned with the rights and obligations of the contracting parties. A transaction that only in form complies with the Shari’ah but not in substance has a different set of consequences for the contracting parties. It may entitle the contracting parties to a set of rights and obligations different from the ones that are intended by the Shari’ah. The paper also relates Islamic deposit and financing transactions to the objectives (maqasid) of Shari’ah and argues that wealth should benefit not only its owner but also the society. The paper concludes that Islamic deposit and financing transactions should entitle the parties to a set of rights and obligations assigned to them by the Islamic law and should become a means for achieving the objectives of Shari’ah.